2020
DOI: 10.1093/genetics/iyaa007
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of cytoplasmic incompatibility factor (cifA and cifB) genetic variation on phenotypes

Abstract: Wolbachia are maternally transmitted, intracellular bacteria that can often selfishly spread through arthropod populations via cytoplasmic incompatibility (CI). CI manifests as embryonic death when males expressing prophage WO genes cifA and cifB mate with uninfected females or females harboring an incompatible Wolbachia strain. Females with a compatible cifA-expressing strain rescue CI. Thus, cif-mediated CI confers a relative fitness advantage to females transmitting Wolbachia. However, whether cif sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 72 publications
(156 reference statements)
1
61
1
Order By: Relevance
“…Other studies have shown infertility induced by cifB alone in D. melanogaster, induced by wPip's Type IV cifB homologue (also called cinB) and by the Type I cifB homologue from wRec, a CI-inducing strain found in Drosophila recens 47,48 . Neither study was able to demonstrate rescue of these effects and thus could not conclude that they were CI related 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown infertility induced by cifB alone in D. melanogaster, induced by wPip's Type IV cifB homologue (also called cinB) and by the Type I cifB homologue from wRec, a CI-inducing strain found in Drosophila recens 47,48 . Neither study was able to demonstrate rescue of these effects and thus could not conclude that they were CI related 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the molecular mechanism at the basis of CI has been recently elucidated: CI displays as embryonic death when a male expressing prophage WO genes cifA and cifB mate with an uninfected female or a female infected by an incompatible Wolbachia strain. In mosquito females harboring a compatible cifA-expressing strain rescue the embryonic development (LePage et al, 2017;Shropshire et al, 2021). Wolbachia has recently been detected in Ae.…”
Section: Wolbachia and The Immune System Of Mosquitoesmentioning
confidence: 99%
“…In our view, our findings are supportive of a parsimonious toxin-antidote model where CifB is the toxin and CifA is the antidote. Lending support to this, other studies have shown some infertility induced by cifB alone in flies, with both w Pip’s Type IV cifB homolog (also called cinB) and w Rec’s Type I cifB gene, though neither study demonstrated rescue of these effects and thus could not conclude that they were CI related 28,29 . While it is plausible that in some systems CifA may stabilize or even potentiate CifB activity, our results rule out that CifA is always necessary for CI.…”
Section: Resultsmentioning
confidence: 97%